Pemanfaatan Fasilitas Kids Art Space Sebagai Strategi Promosi Edukatif Sekolah PAUD Melalui Media Flayer - Icam Sutisna; Yenti Juniari; Sri Indrawati Zakaria; Nur Salsabila Amara; Amelia Gani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This community service activity aims to improve the promotional capabilities of early childhood education (PAUD) schools by utilizing the Kids Art Space facility as an educational medium featured in school flyers. Kids Art Space is a creative learning space that plays a crucial role in developing creativity, fine motor skills, and artistic expression in early childhood. However, this facility has not been optimally utilized as part of the educational institution's promotional strategy. The community service implementation method included initial observations of school facilities, assistance in designing promotional content, and simple training for PAUD teachers and administrators on creating informative and engaging flyers. The results showed that assistance in utilizing Kids Art Space in flyers improved PAUD administrators' understanding of educational promotional strategies and produced promotional media that concretely represented the quality of learning. Flyers featuring children's activities in the Kids Art Space were deemed more communicative and able to attract parents as potential users of educational services. Thus, this community service activity makes a significant contribution in helping PAUD schools optimize learning facilities as a promotional strategy that is not only commercial, but also educational and oriented towards child development.